Primary adenocarcinoma of the appendix: a case report - Kopeć, Bogdan; Kula, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2007)
Primary adenocarcinoma of the appendix is rare, with fewer than 250 cases described in the literature. We report a 46-year-old female patient presenting symptoms of acute appendicitis. The patient underwent a simple appendectomy. Histopathology showed the it was a well-differentiated adenocarcinoma invading the submucosa. She was examined at regular periodic follow-ups and no evidence of recurrence or metastasis was noted in the 7-year postoperative period. Our case shows that well-differentiated adenocarcinoma invading the submucosa may be feasibly treated with simple appendectomy.